Occurrence of juveniles Luvarus imperialis (Actinopterygii: Perciformes: Luvaridae) in the Strait of Sicily - Insacco, Gianni (Array, 2021)
Two juveniles Luvarus imperialis, astrodermella stage, 97.4 mm and 90.6 mm in total length, were recorded on September 2016 and August 2017 respectively, the first caught by a bottom trawler off the south-eastern coast of Sicily, Strait of Sicily, Italy, the second found stranded on the beach in the nearby region. Biometrics data of this uncommon species are given and the occurrence of juvenile stages in the Mediterranean area is briefly discussed.